Blog dan media baru - Mansor, Ruzain Syukur (Persatuan Pustakawan Malaysia, 2010)
Blogging is an alternative means for individuals to share their ideas with the masses. This article identifies patterns of blogs and outlinesthe ethics involved in blogging.